Natural Language Processing (NLP) and Support Vector Machine (SVM) Optimization in Detecting Phishing Website URLs - Mhd Adi Setiawan Aritonang; Maradona Jonas Simanulang; Toras Pangidoan Batubara; Imanuel Zega; M Hafis Afrizal (Informatika, Universitas Jenderal Soedirman, 2026)
Phishing remains one of the most pervasive cyber-threats, with recent reports indicating a sharp rise in both volume and sophistication of attacks. According to the Anti‑Phishing Working Group, phishing incidents reached nearly 1 million in Q4 2024. To address this evolving threat, this study aims to develop an automated phishing-URL classification system based on Natural Language Processing (NLP) and Support Vector Machine (SVM). We utilised the Kaggle